2022
DOI: 10.2196/30682
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Physical Activity and Weight Loss With mHealth Interventions Among Workers: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background Physical activity (PA) is a vital factor in promoting health in the workforce. Mobile health (mHealth) interventions have recently emerged in workplace health promotion as an effective strategy for inducing changes in health behaviors among workers; however, the effectiveness of mHealth interventions in promoting PA and weight loss for workers is unclear. Objective This study aims to provide a comprehensive analysis of current evidence on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…27 Literature reviews have pointed out increased physical activity, better productivity, and higher engagement; however, often, the effects are not significant. 28,29 Additionally, a study by Lowenstyn et al has also reported the potential effectiveness of a medical check-up in combination with the use of web-based information 30 as a new promising measure, supporting our study aim. Some authors have further argued that more studies on the effectiveness of these apps by using a larger number of participants and longer time frames are required.…”
Section: Related Worksupporting
confidence: 83%
See 1 more Smart Citation
“…27 Literature reviews have pointed out increased physical activity, better productivity, and higher engagement; however, often, the effects are not significant. 28,29 Additionally, a study by Lowenstyn et al has also reported the potential effectiveness of a medical check-up in combination with the use of web-based information 30 as a new promising measure, supporting our study aim. Some authors have further argued that more studies on the effectiveness of these apps by using a larger number of participants and longer time frames are required.…”
Section: Related Worksupporting
confidence: 83%
“…Some authors have further argued that more studies on the effectiveness of these apps by using a larger number of participants and longer time frames are required. 28 Other studies have contributed in the field of adoption to gain insights into the potential usage and acceptance of end-users. 24,31 To explain a range of usage behaviors and detect usage approaches, studies have combined available theoretical frameworks and models, such as the theory of planned behavior (TPB) and technology acceptance model (TAM).…”
Section: Related Workmentioning
confidence: 99%
“…Over the past few years, it has become clear that mHealth technologies (eg, apps or SMS) can help to reduce weight loss, improve physical activity, and change behavior [ 5 - 8 ]. Previous reviews evaluated the effectiveness of mHealth interventions in these three domains [ 9 - 12 ]. These reviews suggest that mHealth interventions appear to be promising for preventive and therapeutic activities.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, it has become clear that mHealth technologies (eg, apps or SMS) can help to reduce weight loss, improve physical activity, and change behavior [5][6][7][8]. Previous reviews evaluated the effectiveness of mHealth interventions in these three domains [9][10][11][12]. These reviews suggest that mHealth interventions appear to be promising for preventive and therapeutic activities.…”
Section: Introductionmentioning
confidence: 99%